Searching for Virtue: Physiognomy, Sociability, and Taste in Isabella Teotochi Albrizzi's "Ritratti" - Dalton, Susan (Eighteenth-Century Studies, 2006)
One of the most famous Venetian women of her time, Isabella Teotochi Albrizzi (1760-1836) was known not only for her salon, but also for her published works. One of these pieces, Teotochi Albrizzi's Ritratti (1807), a series of literary portraits, reveals Europe's concern over the simulation of virtue in a society beginning to judge merit by behavior and self-presentation rather than birth. Teotochi Albrizzi's portraits demonstrate the strategies used to discern character and how the author drew on ideas concerning sexual difference in the realm of aesthetics to address concerns raised by shifting practices of sociability.

Gender and the Shifting Ground of Revolutionary Politics: The Case of Madame Roland - Dalton, Susan (Canadian Journal of History, 2001)
Whereas much of the literature on women and the French Revolution continues to see political activity as incommensurate with a desire to behave properly as a woman, studying the correspondence of Marie-Jeanne Roland from 1788 to 1793 shows how she combined political action with respect for gender norms in the last six years of her life. Both while living in the countryside near Lyon and in Paris itself, Roland assumed three roles which she deemed proper to a woman patriot: inciting revolutionary action, formulating policy, and informing others of revolutionary events. The importance of each of these roles shifted with changes in political climate, as did Roland’s conception of what constituted appropriate female behaviour. What made these changes possible was Roland’s ability both to adapt her political strategy to her circumstance and to create a mutable gender code to fit her political needs.

Elisabetta Mosconi's Letters to Giovanni Antonio Scopoli: A Noble Marriage Negotiation at the Turn of the Nineteenth Century in Verona - Dalton, Susan (Lumen: Selected Proceedings From the Canadian Society for Eighteenth-Century Studies, 1999)

Venice's Amazon? Giustina Renier Michiel's Strategic Accommodation of Occupying Forces - Dalton, Susan (Studies in Eighteenth-Century Culture, 2024)
Giustina Renier Michiel, one of the most prolific female authors of early nineteenth-century Italy, is often remembered and celebrated as a Venetian patriot. During her lifetime, however, her literary identity was neither singular nor completely cohesive. Indeed, reading her manuscript writing alongside her more famous publications (including her history of Venetian festivals) illustrates the delicate balance Italian authors needed to maintain in order to ensure their continued literary success in a period marked by multiple and rapid regime changes. While obliged to work within the power structures established by their new political overlords, they nonetheless needed to remain sensitive to the tastes of Italian readers, who were subjected to the political occupation of their territory. Renier Michiel's experience demonstrates how it was possible to balance patriotism, political deference, and professional self-promotion with the goal of establishing a lasting cultural legacy.

Gender, Mediation and Popular Education in Venice, 1760-1830 - Dalton, Susan (Routledge Studies in Eighteenth-Century Cultures and Societies, 2023)
"Gender, Mediation and Popular Education in Venice, 1760-1830 examines how women with enough cultural capital could turn their identity as representatives of "the public" - those on the receiving end of education - to their advantage, producing knowledge under the guise of relaying it. Author Susan Dalton looks at the question of how elite women turned their reputation for ignorance into an opportunity to establish themselves as authors at the dawn of the nineteenth century in Venice. Many literary figures saw women as a group in need of education. By deploying essentialist understandings of femininity, whereby women possessed superior moral virtue but deficient rationality, these women entered the publishing world as cultural mediators, identified by contemporaries as key players in the social projects of public education and moral edification central to the European Enlightenment. Focussing on Isabella Teotochi Albrizzi and Giustina Renier Michiel, both renowned Venetian authors, the author introduces two well-known Italian women of letters to English-speaking scholars; re-evaluates the impact of their writing in Italy and raises questions about female authorship across Europe; broadens our conceptions of gender norms; and enriches our knowledge of a little-known period of women's writing in Italy. This volume is an essential resource for students and scholars alike interested in women's and gender history, early modern history and social and cultural history"--
Keywords: Intellectual life; Intellectual life History; Italy Venice; Salons; Venice (Italy); Women

Isabella Teotochi Albrizzi as Cultural Mediator: gender and writing on art in early nineteenth-century Venice - Dalton, Susan (Women's History Review, 2014)

Engendering the Republic of Letters: Reconnecting Public and Private Spheres in Eighteenth-Century Europe - Dalton, Susan (McGill-Queen's University Press, 2004)
Being women provided them with a particular perspective, expressed first-hand through their letters. Dalton shows how Lespinasse, Roland, Renier Michiel, and Mosconi grappled with differences of ideology, social status, and community, often through networks that mixed personal and professional relations, thus calling into question the actual separation between public and private spheres. Building on the work of Dena Goodman and Daniel Gordon, Dalton shows how a variety of conflicts were expressed in everyday life and sheds new light on Venice as an important eighteenth-century cultural centre.
Keywords: Literary Collections / Letters; Social Science / Women's Studies

Interacting with Print: Elements of Reading in the Era of Print Saturation - The Multigraph Collective; Dalton, Susan (University of Chicago Press, 2018)
A thorough rethinking of a field deserves to take a shape that is in itself new. Interacting with Print delivers on this premise, reworking the history of print through a unique effort in authorial collaboration. The book itself is not a typical monograph—rather, it is a “multigraph,” the collective work of twenty-two scholars who together have assembled an alphabetically arranged tour of key concepts for the study of print culture, from Anthologies and Binding to Publicity and Taste. Each entry builds on its term in order to resituate print and book history within a broader media ecology throughout the eighteenth and nineteenth centuries. The central theme is interactivity, in three senses: people interacting with print; print interacting with the non-print media that it has long been thought, erroneously, to have displaced; and people interacting with each other through print. The resulting book will introduce new energy to the field of print studies and lead to considerable new avenues of investigation.
Keywords: 18th century; =CL; advertising; anthology; author; authorial collaboration; binding; books; catalogs; conversations; cultural studies; culture; ecology; engraving; ephemerality; historical; history; indexes; interactions; intermediality; key concepts; letters; manuscripts; marking; media; monograph; multigraph; paper; print; printing; proliferation; reading; spacing; stages; thickening

Jean Stanislas Mittié et la syphilis - Beaulieu, Léonie (Université de Montréal, 2021)
Jean-Stanislas Mittié, a medical doctor from the Paris region, develops and attempts to gain approval for a vegetal cure to syphilis between 1777 and 1795. The present memoir proposes an analysis of the various textual documents surrounding his endeavours in order to assess the impact of the end of the Ancien Régime and the French Revolution on his medical practice. His individual story reveals the important transformations of institutional, political and cultural power structures regulating medicine at the end of the 18th century.
Keywords: French revolution; History - European / Histoire - Européenne (UMI : 0335); Jean-Stanislas Mittié; Medicine; Révolution française; médecine; syphilis

Engendering the Republic of Letters: Reconnecting Public and Private Spheres in Eighteenth-Century Europe - Dalton, Susan (Université de Montréal, 1999)
Keywords: Histoire

L'autonomie d'un jeune agent révolutionnaire : Marc-Antoine Jullien de Paris, 1789-1794 - Déplanche, Nicolas (Université de Montréal, 2009)
Keywords: France XVIIIe siècle; French Revolution; Marc-Antoine Jullien de Paris (1775-1848); Révolution française; XVIIIth Century France

La France - la race - les colonies : une analyse historiographique en trois temps - Foucher, Maxime (Université de Montréal, 2015)
Ce mémoire a pour objectif d’analyser et de répertorier les productions historiographiques sur la race et le racisme dans l’Atlantique français au XVIIIe siècle. À travers nos lectures, nous avons pu constater que l’historiographie sur les colonies françaises, de plus en plus abondante, et l’approche privilégiant l’espace atlantique ont pris beaucoup d’importance depuis les vingt dernières années et cela a grandement influencé notre choix de diviser les productions historiographiques en trois catégories qui seront les trois chapitres de ce mémoire. Dans un premier temps, nous traiterons des travaux portant plus spécifiquement sur la race et le racisme où nous présenterons le débat quant à l’origine temporelle du racisme. Par la suite, nous présenterons certains travaux en histoire de l’esclavage dans l’Atlantique français qui relient le développement de l’esclavage et celui de la pensée raciale. Finalement, nous aborderons la question du racisme dans la métropole française au XVIIIe siècle en analysant les études qui ont été faites sur les questions des minorités noires et juives en France ainsi que les études sur la question coloniale à l’heure de la Révolution française. Par ailleurs, nous allons aussi présenter le désaccord qu’il y a entre les historiens quant à l’authenticité de la croyance des philosophes des Lumières en leur idéologie prônant la tolérance. Avec les nouvelles productions en histoire atlantique, il est évident que la conception de la race en France est le résultat d’une multitude de facteurs : culturels, scientifiques, économiques et politiques.
Keywords: Black; Colonie; Colony; Eighteenth century; Empire français; Enlightenment; Esclavage; French Empire; Historiographie; Historiography; History - General / Histoire générale (UMI : 0578); Lumières; Noirs; Race; Racism; Racisme; Slave trade; Slavery; Traite des Noirs; XVIIIe siècle

Luttes politiques et références contradictoires à la Révolution durant la Restauration en France, 1814-1820 - Ennemiri, Zakaria (Université de Montréal, 2018)
In 1814, an ending that no one could have anticipated brought back a dynasty swept by the winds of history twenty-five years ago. Returning to France, Louis XVIII restores their titles to the old nobility of the Ancien Régime, but "grants" a Charter which was intended to guarantee the liberal principles inherited from the Revolution. The « Restoration », the name given to the reestablishment on the throne of France of the former Bourbon dynasty, nevertheless raised many questions. What would happen to this new France that had emerged with the Revolution since 1789? Between 1814 and 1820, a period during which a liberal political program was established, the Royalists invoked the Revolution and the threats it put on the monarchy in order to fight it. The Liberals, on the other hand, saw in their royalist adversaries an old and embittered nobility, emerging once more from a distant past, and who badly conceals its secret desire to abolish the Charter and claim her former rights. This master’s thesis will discuss the divide that existed between two elites competing for political and social dominance. In the light of the debates of the time, we will see how Royalists and Liberals, the two major political groups of the period, articulated their speech. One theme appears particularly prominent: the Revolution. After two decades, it divides again. Worse, it was still relevant and its memory never ceased to occupy the political space.
Keywords: Ancien Régime; Bourgeoisie; Censorship; Censure; Cent-Jours; Classe moyenne; Exceptional law; History - European / Histoire - Européenne (UMI : 0335); Hundred Days; Liberalism; Libéralisme; Loi d’exception; Middle class; Nobility; Noblesse; Old Regime; Press; Presse; Regicide; Restauration; Restoration; Royalism; Royalisme; Régicide; Révolution

Le discours sur l'éducation des femmes pendant la Révolution française la représentation de la citoyenneté féminine entre 1789 et 1794 - Laplanche, Laurie (Université de Montréal, 2008)
Keywords: Citoyenneté; Culture; Droit des femmes; France; Moeurs; Politique; Révolution française; Éducation

Quand un peuple juge un roi : la représentation de l'opinion publique et l'image du roi Louis XVI dans les Révolutions de Paris - Ouellet, Simon (Université de Montréal, 2005)
Keywords: Histoire

L'étiquette en sursis : le développement du protocole de cour français durant la phase monarchique constitutionnelle de la Révolution française : 14 juillet 1789 - 10 août 1792 - Racette, David (Université de Montréal, 2006)
Keywords: Cour; Cérémonial; France; Histoire; Protocole; Représentations symboliques; Révolution française; XVIIIe siècle; Étiquette

L’identité et la sexualité queer de Giovanni Bordoni : discours parallèles sur l’homoérotisme féminin et le travestissement en Italie au milieu du 18e siècle - Martel-Dion, Audrey (Université de Montréal, 2023)
This dissertation focusses on the Breve storia, a medical biography published in September 1744 by physician and anatomist Giovanni Bianchi. This novella recounts the life and autopsy of a young Roman servant, Giovanni Bordoni, known in many villages in Tuscany as an enthusiastic seducer and womanizer, until his death on June 28th, 1743. At this point, when the body is stripped for the autopsy, the physician notes female reproductive organs. In fact, even though Bordoni led his adult life under a male identity, his biological sex becomes a subject of discussions and writings after his death, immortalizing him as a woman with same-sex desires, cross-dressed as a man. However, by delving into sexuality and gender as they were understood in early modern Europe, this dissertation deconstructs two main claims: first, that female same-sex desires were intrinsically linked to clitoral hypertrophy, second, that gender existed only in a strict normative link to the biological sex. Thus, by analyzing the Breve storia and Bianchi’s correspondence with his readers, it is possible to shed light on the diverse ways of naming and understanding female homoeroticism in the 18th century, linking it for example with genital anatomy, psychology, and emotions. This master’s thesis highlights that, while the early moderns considered that gender’s essence is found in sex, they could understand it as sometimes fluid, but also as not fully masculine or feminine.
Keywords: 18e siècle; 18th century; =CL; Italie; Italy; Modern history / Histoire moderne (UMI : 0582); gender; genre; histoire; histoire queer; history; homoeroticism; homoérotisme; queer; sexuality; sexualité

Espaces et pratiques de l'activisme politique de Germaine de Staël lors de la Révolution française (1789-1799) - Beausoleil, Marie-Ève (Université de Montréal, 2010)
Ce mémoire explore les modalités culturelles de la participation politique de la salonnière parisienne et célèbre écrivaine Anne-Louise-Germaine Necker, baronne de Staël-Holstein (1766-1817), au cours de la Révolution française (1789-1799). Sur le plan des représentations, il souligne chez Germaine de Staël l’appropriation et la reformulation des normes de genre pour élaborer un rôle politique convenable à une femme d’esprit dans le contexte révolutionnaire. Ce rôle se fondait notamment sur une éthique de l’amitié et un idéal de vertu acquise par la sensibilité et la raison. Son projet constitutionnel, à la fois libéral et élitiste, cherchait à intégrer la contribution des femmes au processus politique à travers la sociabilité polie et la production littéraire. Sur le plan des pratiques, ce mémoire montre comment les outils de réseautage et de communication qu’étaient le salon, la correspondance et la publication fonctionnaient ensemble pour permettre à Staël de se positionner dans un espace sociopolitique et d’y déployer une action. Il considère ces forums comme des éléments constitutifs d’une culture politique révolutionnaire dont Staël sut faire un usage créatif et constructif pour promouvoir ses idées et son parti.
Keywords: Anne-Louise-Germaine Necker de Staël-Holstein (1766-1817); Correspondance; Correspondence; Culture politique; French Revolution (1789-1799); Gender norms; Genre; Histoire; History; History - Modern / Histoire - Moderne (UMI : 0582); Imprimé; Literature; Littérature; Political Culture; Print culture; Révolution française (1789-1799); Sensibility; Sensibilité; Sociability; Sociabilité

La définition de l'homme dans le discours féminin : l'exemple de La Donna galante ed erudita (Venise, XVIIIe siècle) - Brunelle Beauchemin, Odile (Université de Montréal, 2008)
Keywords: 18th century; Femme; Histoire; History; Homme; Italie; Italy; Mariage; Marriage; Men; Périodique féminin; Sociability; Sociabilité; Venice; Venise; Women; Women's magazine; XVIIIe siècle

Vertueuse, mondaine et intellectuelle : la féminité selon Giustiniana Wynne di Rosenberg-Orsini ou une perspective sur le genre à Venise au XVIIIe siècle - Church-Duplessis, Véronique (Université de Montréal, 2009)
Keywords: 18th century; Europe; Femmes; Gender; Genre; Giustiniana Wynne di Rosenberg-Orsini; Giustiniana di Rosenberg-Orsini; Histoire; History; Literature; Littérature; Sociability; Sociabilité; Venice; Venise; Women; XVIIIe siècle

Uni, autoritaire et éclairé : le gouvernement français dans la pensée d'Olympe de Gouges de l'Ancien Régime à la première République, 1785-1793 - De Sève, Étienne (Université de Montréal, 2009)
Keywords: 18th century; Authority; Autorité; France; French Revolution; French government; Gouvernement français; Histoire XVIIIe siècle; History; Olympe de Gouges; Olympre de Gouges; Ordre social; Révolution française; Social order; Unity; Unité

Lire et penser le monde : une analyse numérique d’un long siècle de géographies imaginées dans l’imprimé de langue française (1700-1815) - Laramée, François Dominic (Université de Montréal, 2019)
Historians have tried to determine what francophones read during the long 18th century for over a hundred years. To do so, they have studied library inventories, printing permits, and the archives of printer-editors, but these sources are fragmentary and of uncertain representativeness. This thesis reframes the question by studying, with a combination of computational methods and close reading, large digitized corpora that approximate the entire French-language print market of the long 18th century. Using these vast corpora, the thesis proposes and demonstrates that it is possible to pinpoint ideas to which readers were probably exposed frequently enough that the ideas influenced the readers’ mental maps of the world, regardless of what precise texts were involved in each case. Thus, the thesis shows that digital approaches constitute a major new tool for historians of reading and print, including (under some circumstances) when the only data at their disposal is OCR results plagued with high error rates. As an illustrative case study, the thesis examines imagined geographies, i.e., mental models of the world produced by exposition to print media containing direct or indirect descriptions of territories and their inhabitants. Concepts drawn from psychology, behavioural economics and media studies suggest how readers may have interiorized the messages transmitted by print and used them, consciously or not, to build their own imagined geographies. A study of some 70 000 volumes printed in French between 1700 and 1815, extracted from the Hathi Trust collection, shows that the Europe discussed in print expands eastward with time, that England draws most of the attention, and that discourses regarding most of the European powers are both remarkably stable and centred on war and aristocracy. Studies of major periodicals, cheap popular booklets (the Bibliothèque bleue), geography manuals and Raynal’s Histoire des deux Indes corroborate these findings. Examining the 14,547 geography articles published in Diderot’s Encyclopédie reveals a largely urban imagined geography that changes focus during publication, from Diderot’ purely descriptive science to a tool for cultural transmission when Louis de Jaucourt takes over primary writing duties; a parallel study of 6,053 articles drawn from all fields of knowledge shows that the Encyclopédie describes America as a young world rich in resources, primarily botanical, that are ripe for the taking. The way in which the colonial French Atlantic world is portrayed in the Ancien Régime’s main periodicals suggests that they may have played a role in the French public’s notoriously low interest for emigration to the colonies. Travel narratives of expeditions to the Pacific and around the world show tensions between the step-by-step construction of a utilitarian geography and the need to retain readers’ interest by multiplying picturesque or terrifying anecdotes. In all, print media propose to their readers imagined geographies that treat the outside world with distrust.
Keywords: Atlantic world; Early Modern history; France; History - European / Histoire - Européenne (UMI : 0335); digital history; digital humanities; histoire; histoire numérique; history; humanités numériques; imprimé; lecture; monde atlantique; print; reading; époque moderne

Entre cohésions et divisions : les relations entre femmes auteures en France et en Italie (1770-1840) - Lampron, Eve-Marie (Université de Montréal, 2012)
This thesis documents, catalogues, and analyses relationships between female authors in France and Italy, and between French women and Italian women, from 1770 to 1840. It results from a study of the correspondence and published works of twelve women authors (Anne-Marie de Beaufort d’Hautpoul, Sophie Gay, Félicité de Genlis, Marie-Émilie de Montanclos, Constance Pipelet Salm, Germaine de Staël, Teresa Bandettini, Elisabetta Caminer, Carolina Lattanzi, Diodata Saluzzo, Fortunata Sulgher Fantastici, and Isabella Teotochi Albrizzi) over the course of a period marked by important developments in print culture, the significant involvement of women in the querelle des femmes, and the increased presence of women authors. These transformations, together with the international political upheaval caused by the French Revolution, saw attacks on female authorship pursued with increased vigour. The relationships between women authors within such a context illustrate the challenges faced in implementing a “common action” aimed at defending a female cause (that of female authors) before the advent of the feminist movement. Often described as either “rivals” or “sisters”, this study demonstrates that the nature of relationships between women in this period was in fact far more complex. On the one hand, the community of female authors examined was marked by a certain degree of cohesion. These writers had wide-ranging networks of contacts, and could rely on each other for support in times of crisis. They constructed female literary genealogies and deconstructed the discourse used by others in reference to their community, particularly that relating to the “exceptionality” of and “rivalry” between women authors. On the other hand, significant differences also ran across the membership of these networks, notably in terms of nationality, political opinions, and the position each woman occupied within literary circles. Over and above these social and political divisions, this thesis illustrates the difficulties women faced in reconciling their individual interests (the advancement of their own careers, the divisive impact of their multiple identities with the cohesion of their sex/gender) with those of the collective (legitimizing female authorship). In short, this study examines the ways in which female authors recognized the importance of their community and faced the challenges of maintaining its cohesion, at a time when not only literary activity, but also the political and cultural context in which it was framed, were undergoing great transformation.
Keywords: Eighteenth century; Feminism; Femmes; France; Féminisme; History - European / Histoire - Européenne (UMI : 0335); Italie; Italy; Nineteenth century; Relations; Relationships; Sociability; Sociabilité; Strategies; Stratégies; Women; Women writers; XIXe siècle; XVIIIe siècle; Écrivaines

L’envergure du poète dans la pensée de George Sand - Ramsay-Piérard, Anne (Université de Montréal, 2022)
George Sand, born Aurore Dupin (1804-1876), was one of the most prolific writers of the July Monarchy (1830-1848). Her monumental work focuses on a myriad of subjects, which are often studied from the perspective of the ideal. Among other things, Sand was interested in the notion of the poet-artist, which refers to an ideal artist. This notion, specific to this period, is distinguished from the other poet, which is a writer. While the meaning of the notion of poet-writer is well determined, that of poet-artist is subject to a vague and subjective definition. For her part, Sand considers that the poet-artist designates both an artist and a philosopher. This proposition, which is clearly stated, constitutes a central axis to all the artistic thought that she develops. This is what is explored in the present work, through three themes of George Sand's artistic thought. Each chapter is devoted to one of these themes, with an attempt to organize the artistic thought of Sand. The theme of the brotherhood of the arts will be studied first. This typically romantic theme, omnipresent in Sand's writings, perceives the different disciplines as forming a whole. Then, the hierarchy of arts will be reviewed: George Sand considers that music is the superior discipline, compared to some of her contemporaries who believe that poetry is the superior discipline. Finally, George Sand perceives a figure of genius in her writings, which comes close to the ideal artist. All these themes are studied in close relation to the usual visions found under the July Monarchy.
Keywords: Artiste idéal; Brotherhood of arts; Fraternité des arts; Genius; George Sand; Génie; Hierarchy of arts; History - European / Histoire - Européenne (UMI : 0335); Hiérarchie des arts; Ideal artist; July Monarchy; Monarchie de Juillet; Poet; Poète; Romanticism; Romantisme

«Jeunes filles, voilà vos mères. Soyez dignes d’elles!» : modèles moraux et patriotiques de la femme française dans les biographies collectives féminines (1886-1893) - Le Rouzès-Ménard, Eveline (Université de Montréal, 2022)
As Jules Ferry’s Laws (1881-1882) rendered French primary education secular, mandatory and free, most republican pedagogues designed educational lessons developed on the principle of emulation. By promoting national historical figures and heroes, they mostly sought to provide moral and patriotic models, embodying republican values, to all young boys and girls. Many examples offered in classrooms illustrated and perpetuated a vision of French society based on the sexual division of labor: masculine icons expressed public, military, and political roles while feminine icons revealed private, domestic, and maternal attributes or responsibilities. Previous academic studies on the subject explored almost exclusively the content of primary official textbooks. Meanwhile, feminine models presented in children’s literature, especially within popular collective biographies, have not yet been the object of extensive historical research. Although this literary genre was consumed in great numbers by the public in fin-de-siècle France, it has until recently always been sidelined in academic studies. However, it can be argued that collective biographies showed a significant diversity of role models to French youth. Thereby, this Master’s thesis proposes an analysis of moral, civic, and patriotic icons, which schoolgirls were meant to emulate, included in three collective feminine biographies published during the years following Ferry’s school system reforms (between 1886 and 1893). This study attempts to define the « feminine » and « French » identity shaped by the authors of these books, which recommended less conventional and alternative models, different from traditional examples usually seen in official textbooks of the period.
Keywords: Biographie collective féminine; Enseignement primaire; Female role models; Feminine collective biography; Feminine identity; France; Gender studies; Genre; Grandes femmes françaises; Great French women; Histoire nationale; History - European / Histoire - Européenne (UMI : 0335); Identité féminine; Instruction civique et morale; Modèles féminins; Moral and civic education; National history; Patriotism; Patriotisme; Primary education; Third Republic; Troisième République

Toutes les portes qui menaient à la fortune de cour : stratégies courtisanes et pouvoirs des femmes à la cour de Louis XV - Rose, Fabienne (Université de Montréal, 2004)
Keywords: Cour; Femmes; France; Histoire; Pouvoirs; Représentations politiques; XVIII siècle

Anglo-American Scholarship on Women and Gender in the Risorgimento - Dalton, Susan (La storia di genere in Italia in età moderna: un confronto tra storiche nordamericane e italiane, 2014)
Keywords: Congresses; Historiography; History; Italy; North America; Women; Women historians; Women's studies

Women Worthies? Ascriptions of Masculinity to Exceptional Women Writers in Early Nineteenth-Century Italy - Dalton, Susan (The Palgrave Handbook of Transnational Women’s Writing in the Long Nineteenth Century, 2024)
Biographical writing in the early nineteenth century offers a window onto the malleability of gender norms for Italian women in the period. In the world of letters, women writers deemed worthy of biographical treatment after their deaths were often ascribed masculine traits. Attributes such as intelligence and courage, when they complemented a women’s “feminine essence,” served to illustrate her superiority over her female peers. In this sense, posthumous, laudatory biographies constituted signs of both intellectual and social success of women who could simultaneously abide by the constraints of femininity and move beyond them. The current essay demonstrates the conditions that made departures from gender norms possible following the French Revolution in Venice by studying the cases of Giustina Renier Michiel and Isabella Teotochi Albrizzi.
Keywords: =CL

Les enjeux normatifs de la reconnaissance publique dans la France des Lumières : gloire, célébrité, mérite - Beausoleil, Marie-Ève (Université de Montréal, 2018)
This dissertation examines how and why normative issues about public recognition developed in Enlightenment France. It shows that this question gained significance during the transitional period towards modernity as two important phenomena intersected. On the one hand, Enlightenment thinkers – who questioned the arbitrary foundations of authority – made glory into a process of recognition based on merit, which, in turn, could engender a harmonious and just society. On the other hand, the century saw the advent of a celebrity culture, which enabled the multiplication of famed individuals, especially emanating from the capital’s arts and literary circles. Instead of distinguishing individuals whose merit and useful accomplishments gave rise to unanimous admiration, as the economy of glory would demand, celebrity built upon things such as controversies, revelations about private lives, and the consumption of entertainment. From its inception, celebrity was perceived as a contributing factor to moral degeneracy and as a sign of cultural decay. This dissertation examines moral, aesthetic, and biographical texts that contributed to the creation, promotion, and critique of the economies of public recognition. An analysis of these texts published over a 150-year period – from the Querelle des Anciens et des Modernes to the first third of the nineteenth century – sheds light on their arguments with regards to the type of order (literary, social, or political) that they hoped to consolidate or engender. These texts offer a unique view into the particularities of this defining moment shaped by the elimination of traditional hierarchies and the advent of individuals as autonomous moral subjects. This dissertation historicises modern celebrity culture through an examination of its representations and of the conflicts it generated. Although celebrity has been theorized as a media phenomenon that creates a relationship of intimacy between famed individuals and the public, this study shows that, during the period in question, it was largely conceived as a deregulation of glory’s economy of feelings. This economy was based on a theory of moral sentiments that enabled the natural recognition of true merit, and that would, in due course, solve the tension between the subjectivity of opinions and the objectivity of values. To the contrary, celebrity fuelled passions – such as envy, ambition, and greed – which prompted the creation of immediate and undeserved renown. Celebrity was inscribed in a coherent set of aesthetic and sociocultural manifestations – including, fashion, rococo, bel esprit, satire, persiflage, light reading, cabals, and spectacles – while its systematic definition took shape through a critique of elite mores.
Keywords: 18th century; Celebrity; Critique littéraire; Célébrité; Decline; Décadence; France; Gloire; Glory; History - Modern / Histoire - Moderne (UMI : 0582); Literary criticism; Merit; Moeurs; Mores; Mérite; Public recognition; Reconnaissance publique; XVIIIe siècle; Émotions

Fraternité et métaphore familiale : la Révolution française et la Grande-Colombie - Van Hooren, Justin (Université de Montréal, 2007)
Keywords: Fraternité; Indépendance latino-américaine; Pacte social; Révolution française; Révolutions atlantiques

Giustina Renier Michiel and Conflicting Ideas of Gender in Late Eighteenth-Century Venice - Dalton, Susan (Italy’s Eighteenth Century: Gender and Culture in the Age of the Grand Tour, 2009)
In the age of the Grand Tour, foreigners flocked to Italy to gawk at its ruins and paintings, enjoy its salons and cafés, attend the opera, and revel in their own discovery of its past. But they also marveled at the people they saw, both male and female. In an era in which castrati were "rock stars," men served women as cicisbei, and dandified Englishmen became macaroni, Italy was perceived to be a place where men became women. The great publicity surrounding female poets, journalists, artists, anatomists, and scientists, and the visible roles for such women in salons, academies, and universities in many Italian cities also made visitors wonder whether women had become men. Such images, of course, were stereotypes, but they were nonetheless grounded in a reality that was unique to the Italian peninsula. This volume illuminates the social and cultural landscape of eighteenth-century Italy by exploring how questions of gender in music, art, literature, science, and medicine shaped perceptions of Italy in the age of the Grand Tour.
Keywords: History / Europe / Italy

Urban governance in Montreal and Toronto in a period of transition - Dagenais, Michèle (Urban Governance: Britain and Beyond Since 1750, 2000)
This chapter provides an overview of the situation in Montreal and Toronto in the second half of the nineteenth century, a time when municipal government was